Analysis of Service Levels on Gojek Customer Satisfaction in the Period After the Covid-19 Pandemic - Nia Eliza; Yanti Putri; Firman Priyanto (Yayasan Gema Bina Nusantara, 2023)
This research aims to analyze the differences that consumers can feel regarding the differences in the Gojek application before the pandemic, during the pandemic, and after the pandemic. The type of research carried out is quantitative research, usually referred to as using calculated numbers. The population in this study were all 30 Go-Jek application users. In taking samples using the census sampling technique, namely taking samples based on the existing population. The sample in this study amounted to 30 people. The primary data source used in this research is the results of questionnaires filled out by respondents. The data analysis method that will be used in this research is quantitative analysis. In this research, data analysis will use descriptive statistical techniques and multiple linear regression models. The services provided by Gojek do not have a significant influence on the satisfaction of customers using the Gojek application, which means that Gojek has carried out or fulfilled customer desires very well, which has been proven in the results of our questionnaire in the average indicator, which states strongly agree in every question given.